Studying fission neutrons with 2E-2v and 2E - Al-Adili Ali (EPJ Web of Conferences, 2018)
This work aims at measuring prompt-fission neutrons at different excitation energies of the nucleus. Two independent techniques, the 2E-2v and the 2E techniques, are used to map the characteristics of the mass-dependent prompt fission neutron multiplicity, v(A), when the excitation energy is increased. The VERDI 2E-2v spectrometer is being developed at JRC-GEEL. The Fission Fragment (FF) energies are measured using two arrays of 16 silicon (Si) detectors each. The FFs velocities are obtained by time-of-flight, measured between micro-channel plates (MCP) and Si detectors. With MCPs placed on both sides of the fission source, VERDI allows for independent timing measurements for both fragments. 252Cf(sf) was measured and the present results revealed particular features of the 2E-2v technique. Dedicated simulations were also performed using the GEF code to study important aspects of the 2E-2v technique. Our simulations show that prompt neutron emission has a non-negligible impact on the deduced fragment data and affects also the shape of v(A). Geometrical constraints lead to a total-kinetic energy-dependent detection efficiency. The 2E technique utilizes an ionization chamber together with two liquid scintillator detectors. Two measurements have been performed, one of 252Cf(sf) and another one of thermal-neutron induced fission in 235U(n,f). Results from 252Cf(sf) are reported here.